ANALYSIS OF LISTENING TO CLASS A STORY TEXTS COMBINATION OF LISTENING AND DOING TECHNIQUES AND ONLINE LECTURE METHODS - Irena Mulyana S; Rima Ayu A; Siti Zahra S; Yuni Ertinawati (Media Inovasi Pendidikan dan Publikasi, 2024)
Language is an important tool in human communication, which involves language skills such as listening, speaking, reading and writing. Listening skills, in particular, are an important aspect of interpersonal communication, which involves using the senses to understand the message conveyed. This ability is needed to obtain information and understand the meaning of oral communication. Although listening skills develop naturally, this also requires practice and hard work. This research uses qualitative descriptive methods and questionnaire techniques to evaluate the use of the Listen to Work (SK) technique and lectures in learning to listen to short story texts. The results showed that SK was effective in enabling students' active participation, while lecture was efficient in conveying information directly. However, both methods have their drawbacks, such as the time required and lack of direct interaction. It is recommended to integrate the two methods wisely in designing learning to listen to short story texts. Teachers can start with a lecture session to convey basic concepts, followed by SK activities that allow students to apply those concepts. In this way, students can gain a deep understanding while remaining actively involved in learning.